2020
DOI: 10.1186/s12882-020-01720-0
|View full text |Cite
|
Sign up to set email alerts
|

Supporting quality care for ESRD patients: the social worker can help address barriers to advance care planning

Abstract: Background Advance Care Planning (ACP) is essential for preparation for end-of-life. It is a means through which patients clarify their treatment wishes. ACP is a patient-centered, dynamic process involving patients, their families, and caregivers. It is designed to 1) clarify goals of care, 2) increase patient agency over their care and treatments, and 3) help prepare for death. ACP is an active process; the end-stage renal disease (ESRD) illness trajectory creates health circumstances that ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Raychev et al [ 21 ] have pointed out that only 9% of CI patients can be completely cured after symptomatic treatment, and most patients experience sequelae after treatment, which not only affects the recovery of the disease but also further increases the physical and mental pressure of the patients. Relevant literature has confirmed that efficient nursing intervention for ACI patients can effectively boost the rehabilitation effect [ 22 ]. Routine nursing mode can only provide the patients with nursing services within the regulations, failing to meet their request for diversified nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Raychev et al [ 21 ] have pointed out that only 9% of CI patients can be completely cured after symptomatic treatment, and most patients experience sequelae after treatment, which not only affects the recovery of the disease but also further increases the physical and mental pressure of the patients. Relevant literature has confirmed that efficient nursing intervention for ACI patients can effectively boost the rehabilitation effect [ 22 ]. Routine nursing mode can only provide the patients with nursing services within the regulations, failing to meet their request for diversified nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Case management involves referrals to community resources, outpatient providers, and social service workers. Finally, depending on the setting, HSWs contribute to discharge or ongoing care planning to improve health [14]. The quality and quantity of social work's contribution in these roles is dictated by CMS, making social work integral and necessary in healthcare settings [12].…”
Section: Background 21 Healthcare Social Workmentioning
confidence: 99%
“…ebooklets Informative, attractive designs can arouse curiosity, so that students can easily understand what is conveyed in the learning process. The development of learning media e-booklet has the aim of stimulating students' interest in the learning process, increasing students' reading interest to improve students' cognitive learning outcomes (Senteio, 2020;& Delafontaine et al, 2022).…”
Section: Table 3 the Value Of N-gain In The Experimental Class On Stu...mentioning
confidence: 99%